BIOETHICS AND PATIENT INVOLVEMENT IN MEDICAL DECISION-MAKING: CHALLENGES AND ETHICAL IMPLICATIONS IN CLINICAL PRACTICE - Sari, Restiana Mustika (Universitas Airlangga, 2024)
Background Patient involvement in medical decision-making has become an integral element in contemporary healthcare, affirming the rights and autonomy of patients in their care processes. This review presents an in-depth study concerning the issue of patient involvement in medical decision-making from a bioethical perspective, as well as exploring the challenges and ethical implications that arise in clinical practice. Methods A literature review method is used in this study, encompassing various literary sources that detail bioethical principles such as patient autonomy, justice, beneficence, and non-maleficence in the context of medical decision-making. Additionally, this study seeks a profound understanding of how clinical practices and health policies influence patient involvement and present specific ethical challenges. Result The findings of this literature review highlight the crucial role of bioethics in shaping more ethical practices in medical decision-making and identify key issues that need attention, such as inequality in access and information, value conflicts between patients and healthcare providers, and the need to focus on the best interests of the patient. Conclusion By understanding these ethical challenges and implications, we can better develop guidelines and policies that support meaningful and ethical patient involvement in clinical practice. Thus, this research contributes to the development of healthcare that respects bioethical values as well as the rights and needs of patients.